Arbuscular mycorrhizal potential and mycorrhizal fungi diversity associated with Agave potatorum Zucc. in Oaxaca, Mexico. Issue 2 (7th December 2012) - Carballar‐Hernández, S.; Palma‐Cruz, F. J.; Hernández‐Cuevas, L.; Robles, C.
Abstract: The status of the arbuscular mycorrhizal association in wild Agave potatorum Zucc. was studied at three semiarid sites over a 1‐year period of rhizospheric soil sampling. Root colonization present at all sites and at all times of year, ranged from 20 to 83 %. The extraradical mycelia length was estimated to be from 2.64 to 5.22 m g −1 of dry soil. Spore number ranged from 20 to 192 in 100 g of soil. The number of viable mycorrhizal propagules ranged from 500 to 2, 640 in 100 g of soil. Twenty species of arbuscular mycorrhizal fungi (AMF) were identified, the family Glomeracea comprising the greatest number of species (45 %). Two other fungi families Acaulosporaceae and Gigasporaceae made up 35 and 15 %, respectively. High alpha diversity and low beta diversity of AMF were found in this study. Arbuscular mycorrhizal fungi species richness in A. potatorum is high and the associated fungi appear to be an important component in semiarid ecosystems in this region of Mexico. Arbuscular mycorrhizal fungi species with small spores might be better adapted to the local environment.